Voices of Change: Single-Teacher Primary Schools Perspectives on Multigrade Pedagogy in Balochistan - Arif, Muhammad; Shaoan, Md Mirajur Rhaman; Ismail, Aneta; Okafor, Miracle Uzochukwu; Jamil, Bushra (Asia Social Issues, 2025)
Multigrade pedagogy, which involves instructing students from multiple grade levels in a single classroom, presents both unique challenges and opportunities for educators. This qualitative study explores the perceptions, strategies, and challenges faced by single-teacher primary school educators in Balochistan, Pakistan, within multigrade teaching environments. Grounded in Vygotsky’s sociocultural theory, the study employs an ethnographic approach to gain in-depth insights into teachers’ lived experiences. Data were collected through semi-structured interviews with 10 experienced single-teacher primary school instructors, complemented by classroom observations to capture teaching methods and classroom dynamics. The findings reveal that teachers face significant challenges, including classroom management difficulties, resource limitations, and the need to address diverse learning needs. However, they demonstrate resilience and adaptability, employing collaborative learning, differentiated instruction, and innovative resource utilization to enhance student learning. Despite these challenges, multigrade pedagogy fosters student independence, a strong sense of community, and instructional flexibility. The study highlights the urgent need for targeted teacher training, policy support, and improved resources to enhance the effectiveness of multigrade teaching. Additionally, it suggests avenues for future research, particularly on student learning outcomes and best practices in resource-constrained educational settings.